“Some thought they were ‘in Love’”: Sex, White Teenagehood, and Unmarried Pregnancy in Early Postwar Canada - Wall, Sharon (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2014)
This article explores the culture of postwar heterosexuality as it impacted (mainly) white girls who were teens between 1945 and the early 1960s. It explores the prevalence of, and changing opportunities for teenage sex, the issue of sexual desire, and the nature of girls’ partners and relationships. Based on this exploration, it argues that opportunities for teen sex were expanding, that girls’ partners were more often other teens, and because of this and the age-consciousness of the times, that marriage was being questioned as the appropriate solution when pregnancy occurred. More broadly, this study challenges the (now aging) stereotype of the conservative “Fifties,” especially the notion of this period as a sexually conservative one. As such, it also helps to connect (rather than to contrast) the 1950s with the decade that followed. Finally, it makes the case for an expanded notion of sexual “revolution,” one which unfolded over several decades of the twentieth century. In early postwar years, this was a revolution of behaviour only for unlike “the Sixties,” there was little public acceptance or open avowal of pre-marital sex.